ЦЕНТР КОЛЛЕКТИВНОГО ПОЛЬЗОВАНИЯ «ФИЗИКА И ТЕХНОЛОГИИ НАНОСТРУКТУР»: ФУНКЦИИ И ЗАДАЧИ - Valeriy G. Sozanov; Aleksandr P. Bliev; Tamerlan T. Magkoev (Высшее образование в России)
The role of the Center for collective use of North-Ossetian State University “The physics and technology of nanostructures” in the scientific net of Russian Federation is analyzed. It is shown that adhering to the federal development strategy of CCU net, the North-Ossetian center on the basis of equipment acquiring scientific infrastructure development and attracting youth to science, takes a significant place in realization of priority directions of scientific-technological complex of Russia development, solving the priority scientific tasks, preparation of personnel of higher qualification and creation of the elements of innovative educational environment for higher education.